Superior properties of LaFe₁₁.₈Si₁.₂/La₆₅Co₃₅ magnetocaloric composites processed by spark plasma sintering - Zhong, Xichun (2023)
A series of LaFe11.8Si1.2/La65Co35 bulk composites were fabricated by spark plasma sintering (SPS) followed by diffusion annealing. The effect of sintering temperature (1073-1223 K) on the magnetocaloric and other properties of LaFe11.8Si1.2/La65Co35 bulk composites were investigated. The 1:13 phase content in all the annealed samples was ∼90 wt%. The mechanical and magnetocaloric properties of these annealed bulk composites could be improved by tuning the sintering temperature. The Curie temperature (TC) and maximum magnetic entropy change (-ΔSM)max of the annealed samples varied in the range of 211-228 K and 5.56-9.33 J kg-1 K-1, respectively. Selected samples exhibited excellent mechanical and magnetocaloric properties. The (-ΔSM)max value was 9.33 J kg-1 K-1 at TC of 217.8 K. Its maximum compressive strength (σbc)max value was 540 MPa at a strain of 3.48%, which exceeded the mechanical properties of most La-Fe-Si based bulk composites prepared by hot-pressing sintering (HPS). Thus, La-Fe-Si based bulk composites with good comprehensive properties could be obtained by combining SPS and diffusion annealing.